Translation and Cultural Adaptation into Portuguese of the Quality of Dying and Death Scale for Family Members of Patients in Intensive Care Units - Meneguin, Silmara [UNESP]; Benichel, Cariston Rodrigo [UNESP]; Morais, José Fausto; de Oliveira, Cesar (MDPI, 2022)
The translation and cultural adaptation of the Quality of Dying and Death in Brazil may provide a reliable and reproducible scale for collecting and analyzing data on the process of dying and death, given the absence of Brazilian studies that have produced or used scales in this topic. The purpose of this study was to perform the translation and cultural adaptation of the Quality of Dying and Death (QODD 3.2a) scale for intensive care patients’ relatives into Portuguese (Brazil). This methodological study was carried out in a public university of the São Paulo State University (UNESP) medical school, São Paulo, Brazil, in three stages: translation and back-translation by two native-speaking independent professionals, analysis by a committee of specialists, and a pre-test phase. The final version was created by seven experts after making semantic, idiomatic, and cultural changes to 16 items. The results indicated a satisfactory content validation index (CVI ≥ 0.80). This version was applied on 32 relatives of patients who were hospitalized in a public hospital in the interior of São Paulo. No item was excluded from the instrument. The content and face validity were achieved to a satisfactory standard, in addition to reaching the minimum parameters recommended in the literature. The Portuguese version of QODD 3.2a for relatives of deceased patients in intensive care is appropriate and culturally adapted for use in Brazil.
Keywords: Cross-cultural adaptation; Death; Intensive care; Quality of dying and death scale; Translation; Validation studies